Supramolecular Dispersive Liquid-Liquid Microextraction and Determination of Copper by Flame Atomic Absorption Spectrometry - Luo, Tao; Li, Yingtang; Liu, Chang; Liu, Mousheng (Asian Journal of Chemistry, 2014)
A simple, safe, environmentally friendly, rapid and inexpensive method based on supramolecular dispersive liquid-liquid microextraction (SM-DLLME) was developed for the preconcentration and separation of copper in water samples prior to flame atomic absorption spectrometry analysis. The 1-(2-thiazolylazo)-naphthol was selected as chelating reagent to react with copper, and the supramolecular solvent which was proposed for dispersing and extracting solvent was made up of nonanoic acid, tetrahydrofuran and water. Some influential factors affecting the analytical performance were studied. Under the optimum conditions, the calibration graph was linear in the range of 10-800 μg L-1, the limit of detection (LOD) was 0.3 μg L-1 for copper, the relative standard deviations (RSD, n = 6) was 2.6 %, respectively. The satisfactory relative recoveries (93.5-101.5 %) were achieved after the determination of copper in water samples.